Lactase deficiency in children - N.V. Nagorna; Ye.V. Bordyugova; G.V. Dubova (Zaslavsky O.Yu., 2012)
In this paper the etiological, pathogenetic, clinical, laboratory and instrumental characteristic of lactase deficiency in children are presented. The features of feeding/nutrition, treatment of children with this disease are described. The own clinical observations of patients with lactase deficiency are presented.